2013
DOI: 10.4040/jkan.2013.43.3.420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Kegel Exercise to Prevent Urinary and Fecal Incontinence in Antenatal and Postnatal Women: Systematic Review

Abstract: Purpose: The aim of this study was to review the literature to determine whether intensive pelvic floor muscle training during pregnancy and after delivery could prevent urinary and fecal incontinence. Methods: Randomized controlled trials (RCT) of low-risk obstetric populations who had done Kegel exercise during pregnancy and after delivery met the inclusion criteria. Articles published between 1966 and 2012 from periodicals indexed in Ovid Medline, Embase, Scopus, KoreaMed, NDSL and other databases were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 23 publications
(13 reference statements)
0
16
0
Order By: Relevance
“…The success of Kegel exercises relies on the adequate application of the technique and a strict observance of the exercise program. Today, the conclusion is that, according to some evidence, Kegel exercises may prevent urinary and fecal incontinence in prenatal and postnatal women [16].…”
Section: Clinical Reasonsmentioning
confidence: 99%
“…The success of Kegel exercises relies on the adequate application of the technique and a strict observance of the exercise program. Today, the conclusion is that, according to some evidence, Kegel exercises may prevent urinary and fecal incontinence in prenatal and postnatal women [16].…”
Section: Clinical Reasonsmentioning
confidence: 99%
“…Performing a antenatal perineal massage by the woman or her partner a few weeks prior to the delivery has been advocated to increase elasticity and reduce the risk of perineal trauma from episiotomy or spontaneous tears [4] On the other hand, Dr. Arnold Kegel in 1940 discovered the squeeze and hold vaginal exercises known as Kegel's were specifically designed to target pelvic floor strengthening. Moreover, it is suggested that, since damage due to vaginal delivery occur in supportive pelvic issues and in the nervous structures related to them, the Kegel exercises reduce the laceration rate occurring during vaginal delivery, give vaginal and perineal muscles their previous tones, decrease the edema in perineal region, accelerate the circulation and prevent the stretch of abdominal muscles thereby prolapse and backache, as well as preventing the known stress incontinence [11] [23]- [28].…”
Section: Introductionmentioning
confidence: 99%
“…Kegel training can enhance pelvic floor muscle myodynamics and promote pelvic blood circulation, and helps with natural delivery. Kegel training also prevents postpartum urinary incontinence and postpartum vaginal relaxation, and improves postpartum sexual life [40,41].…”
Section: Discussionmentioning
confidence: 99%